2019
DOI: 10.1007/s00521-019-04500-6
|View full text |Cite
|
Sign up to set email alerts
|

Sparse coding predicts optic flow specificities of zebrafish pretectal neurons

Abstract: Zebrafish pretectal neurons exhibit specificities for large-field optic flow patterns associated with rotatory or translatory body motion. We investigate the hypothesis that these specificities reflect the input statistics of natural optic flow. Realistic motion sequences were generated using computer graphics simulating self-motion in an underwater scene. Local retinal motion was estimated with a motion detector and encoded in four populations of directionally tuned retinal ganglion cells, represented as two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Sparse coding networks have been widely employed in modeling receptive fields and response properties 17,38,39 , and more recently have been applied to local connectivity in visual cortex. Sparse coding argues that the brain is optimized to represent stimuli efficiently such that only a small number of neurons are strongly activated at a given time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sparse coding networks have been widely employed in modeling receptive fields and response properties 17,38,39 , and more recently have been applied to local connectivity in visual cortex. Sparse coding argues that the brain is optimized to represent stimuli efficiently such that only a small number of neurons are strongly activated at a given time.…”
Section: Discussionmentioning
confidence: 99%
“…The key contribution of the present work is in uniting different aspects of both short-range and long-range V1 connectivity with neuronal feature preferences under a single unsupervised learning objective. Sparse coding networks have been widely employed in modeling receptive fields and response properties 17,38,39 , and more recently have been applied to local connectivity in visual cortex. Sparse coding argues that the brain is optimized to represent stimuli efficiently such that only a small number of neurons are strongly activated at a given time.…”
Section: Comparison To Other Normative Modelsmentioning
confidence: 99%
“…We believe that the selectivity for patterns that are linked to physical causes is a general property of sparse representations of sensory data. For example, we have recently shown that applying sparse coding to optic flow data yields rather unexpected kernel shapes, which are tuned to directions of egomotion (Ecke et al, 2020). Screening for such selectivities can be a starting point for identifying the cues that are at the core of inference and it can yield predictions for properties of processing in diverse biological systems.…”
Section: The Link Between Image Statistics and Inferencementioning
confidence: 99%